An examination into the principles of currency involved in the Bank Charter Act of 1844 - Cairnes, John E. (Statistical and Social Inquiry Society of Ireland, 1854)
The prospects of the country at the present moment, on the opening of a European war, present many aspects of anxious interest, and afford indications of a revival of many subjects of discussion, as well of an economical and financial as of a political character, which have long been allowed to slumber in silence. Amongst these we may expect to find our monetary laws pretty severely canvassed; and it is certain that the necessity of supporting large military expenditure in foreign countries is a circumstance of precisely that kind which is likely to bring these laws to a severe test. We have already parted with some four or five millions of bullion in discharge of foreign liabilities of one kind or another; and though the exchanges may have rallied for the present, it is not possible that the country should carry on its warlike proceedings on the scale which seems to be contemplated, without becoming subject to occasional drains of the precious metals of a more extensive character than we have for many years experienced. The occasion, therefore, seems not to be unsuitable for inviting public attention to a consideration of the principles upon which our currency laws are based. These principles, so far at least as regards the control of our paper circulation, are embodied in the Bank Charter Act of 1844. Into all the provisions of that Act it is not intended in the following observations to enter: the points which it is proposed to discuss are those only which affect the central establishment in London; according to which an artificial limit, prescribed by the legislature, is placed upon the issue of notes payable on demand.
The substance of the following pamphlet was read before the Dublin Statistical Society, on the 19th of June last.
Keywords: Bank notes; Bank charter act; 314.15